2022
DOI: 10.3390/membranes12111156
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Membrane-like 2D A’-MoS2 as Anode for Lithium- and Sodium-Ion Batteries

Abstract: Currently, new nanomaterials for high-capacity lithium-ion batteries (LIBs) and sodium- ion batteries (SIBs) are urgently needed. Materials combining porous structure (such as representatives of metal–organic frameworks) and the ability to operate both with lithium and sodium (such as transition-metal dichalcogenides) are of particular interest. Our work reports the computational modelling of a new A’-MoS2 structure and its application in LIBs and SIBs. The A’-MoS2 monolayer was dynamically stable and exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The ion named Ligand, which is attached to molybdenum through a coordinate bond is responsible for the metastable structure and metallic conductivity of 1T MoS2 in which three d orbitals which are degenerated are settled by two electrons. An early theoretical study showed that monolayer MoS2 can have a higher Na adsorption when compared to bulk MoS2 [39]. It is perfect as an anode electrode in Na-ion batteries, with a theoretical capacity of 335 mAhg -1 .…”
Section: Molybdenum Disulphide (Mos2)mentioning
confidence: 99%
“…The ion named Ligand, which is attached to molybdenum through a coordinate bond is responsible for the metastable structure and metallic conductivity of 1T MoS2 in which three d orbitals which are degenerated are settled by two electrons. An early theoretical study showed that monolayer MoS2 can have a higher Na adsorption when compared to bulk MoS2 [39]. It is perfect as an anode electrode in Na-ion batteries, with a theoretical capacity of 335 mAhg -1 .…”
Section: Molybdenum Disulphide (Mos2)mentioning
confidence: 99%
“…15 Although MoS 2 monolayers can be utilized as an electrode, especially when heterostructures are made from it, the absence of good intrinsic conductivity restricts its electrochemical performance. MoS 2 monolayers have a large band gap of 1.7 eV 16 and are semiconducting in nature. 17 The layered hexagonal boron nitride (hBN), 18 which is isostructural to graphite, possesses characteristics that are similar to those of graphite.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although MoS 2 monolayers can be utilized as an electrode, especially when heterostructures are made from it, the absence of good intrinsic conductivity restricts its electrochemical performance. MoS 2 monolayers have a large band gap of 1.7 eV and are semiconducting in nature …”
Section: Introductionmentioning
confidence: 99%
“…In this stoichiometry, multiple phases have been experimentally observed—the hexagonal H phase and the tetragonal T and T’ (or Td) phases, which exhibited completely different electronic properties: in the case of MoS 2 , the H phase is a semiconductor, while the T phases are metals. Furthermore, several metastable TMD phases have been theoretically proposed, among which are the square-octagonal (S) and disordered square-octagonal (S’) monolayers [ 4 ], another hexagonal H’ phase [ 5 ], and a triclinic-structured A’ phase [ 6 , 7 ]. Moreover, several non-stoichiometric monolayers in the M-X system have been proposed [ 8 , 9 , 10 , 11 ] and some of them successfully fabricated [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%